2017
DOI: 10.1038/srep40090
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive three monoclonal antibodies based automatic latex particle-enhanced turbidimetric immunoassay for Golgi protein 73 detection

Abstract: Golgi protein 73 (GP73) is a novel and potential marker for diagnosing hepatocellular carcinoma (HCC) that has been found to be abnormally elevated in liver disease. A latex particle-enhanced turbidimetric immunoassay (LTIA) was recently introduced and licensed for application in a variety of automated clinical chemistry analyzers. However, no studies have reported sufficient data on analytical performance of this method when using 3 monoclonal antibodies for GP73 measurement. The experimental conditions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In addition, the GP73 content in serum from 80 cases of liver cancer and 80 healthy people was detected by latex‐enhanced immunoturbidimetric method based on polyclonal antibody, with 94.6% sensitivity and 72.4% specificity. The use of three monoclonal antibody‐based latex‐enhanced immunoturbidimetric assays has a 96.7% sensitivity and 93.3% specificity . These two methods can be more easily automated, and they are faster than ELISA therefore have very good clinical application prospects.…”
Section: Detection Methods For Gp73mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the GP73 content in serum from 80 cases of liver cancer and 80 healthy people was detected by latex‐enhanced immunoturbidimetric method based on polyclonal antibody, with 94.6% sensitivity and 72.4% specificity. The use of three monoclonal antibody‐based latex‐enhanced immunoturbidimetric assays has a 96.7% sensitivity and 93.3% specificity . These two methods can be more easily automated, and they are faster than ELISA therefore have very good clinical application prospects.…”
Section: Detection Methods For Gp73mentioning
confidence: 99%
“…It is also known as Golgi membrane protein I or Golgi phosphor protein 2. Because its relative molecular mass in polyacrylamide gel electrophoresis is 7.3 × 10 4 , it is also called GP73 . At present, many studies have found that the GP73 protein is associated with liver diseases, especially with liver cancer diseases; therefore, it is expected to become a new serological tumour marker for early diagnosis of liver cancer, which has attracted widespread attention from research scholars.…”
Section: Introductionmentioning
confidence: 99%
“…PETIA is one of the homogeneous immunoassays well adopted in clinical research . The assay typically uses monodisperse latex beads of 100–200 nm in diameter to enhance light-scattering signals due to aggregation of the antibody-conjugated particles in the presence of target antigens in a sandwich configuration. Sample concentrations of 0.5 mg/L or less have been measured with good precision and high reproducibility. Compared with other commonly used immunodiagnostic methods such as enzyme-linked immunosorbent assay (ELISA) and lateral flow immunoassay (LFIA), PETIA has several distinct advantages such as rapid (within 10 min), simple (single-step and washing-free), reproducible (small coefficient of variation), and automatable .…”
Section: Introductionmentioning
confidence: 99%
“…In short, the detection is expected to proceed in the antibody excess zone, where the antibody–antigen precipitation has positive correlation with the antigen. At the present time, the conjugations of the reagent with nanomaterials such as latex particles [ 25 , 26 ] and nanogold [ 27 , 28 ] have been made, to enhance immunoturbidimetry sensitivity, but the biochemical conjugation process is relatively complicated. The convenient, simple and easy-to-operate NanoPITA method can be more suitable for ultrasensitive, rapid, and accurate analysis of protein markers, showing great potential in early clinical diagnosis of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%